The Effect of Library Service Digitalization on the Ease of Information Access for Users at the Regional Archives and Library Office of West Sumatra Province - Lioni, Lioni; Rahmah, Elva (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the limited empirical understanding of the extent to which library service digitalization influences users’ ease of access to information. Although various digital services have been implemented, their effectiveness in improving information accessibility requires systematic investigation. This study aims to examine the effect of library service digitalization on users’ ease of information access at the Regional Archives and Library Office of West Sumatra Province. A quantitative approach with an associative method was employed. The population consisted of 17,410 digital service users during the October–December 2025 period, from which 100 respondents were selected using simple random sampling. Data were collected through a Likert-scale questionnaire and analyzed using normality testing, linearity testing, Pearson correlation, simple linear regression, and coefficient of determination with SPSS. The findings indicate that library service digitalization has a significant effect on users’ ease of access to information (Sig. = 0.000 < 0.05). The correlation coefficient of 0.547 shows a moderately strong positive relationship, while the coefficient of determination of 0.300 indicates that digitalization contributes 30% to users’ ease of information access, with the remaining 70% influenced by other factors. These findings demonstrate that library service digitalization plays an important role in enhancing information accessibility for users. This study contributes to the literature on digital library services by providing empirical evidence of the relationship between service digitalization and information access. Practically, the findings imply the need to strengthen digital infrastructure, improve librarians’ digital competencies, and expand digital collections to optimize technology-based library services.